Inklusi Sosial Kaum Difabel dalam Perspektif Al-Quran: Analisis Kontesktual Surah ‘Abasa - Mochamad Aris Yusuf (Mustaneer : Journal of Islamic Thought and Civilization, 2025)
This study aims to examine the social inclusion of people with disabilities from the perspective of the Qur'an with a focus on the contextual analysis of Surah 'Abasa. People with disabilities often experience marginalization and discrimination from society, especially by groups considered "normal" physically and mentally. This study uses a qualitative-descriptive method with an approach to studying the Qur'an and Hadith. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the study show that the Qur'an, especially in Surah 'Abasa, pays great attention to the existence of people with disabilities and guarantees their rights in social life, including access to education and decent social participation. The Qur'an views people with disabilities as equal to other humans in terms of dignity and respect. Therefore, discrimination against them is contrary to the principles of justice and humanity in Islam. This study emphasizes that the inclusive values ​​in the Qur'an must be used as a basis for building a just and disabled-friendly society.